The Authority of Regency/City Governments in Control of Alcoholic Beverage Sales - Hadi, Syofyan (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
The purpose of this research is to analyze the authority of the Regency/City Government in controlling the sale of alcoholic beverages. This research is a normative legal research using a statutory approach and a conceptual approach. Primary legal materials were collected by inventorying and categorizing laws and regulations, while secondary legal materials were collected through literature studies. Legal materials were analyzed using normative analysis. The results of the study found that the Regency/City Government is given attribution authority to control the sale of alcoholic beverages in the form of (1) Authority to provide SIUP-MB class B and C for retailers and direct sellers of drinks on the spot and (2) Authority to determine certain places that are permitted or restricted or prohibited from selling and distributing alcoholic beverages in accordance with regional characteristics in accordance with the provisions of Article 12 paragraph (3) of Law No. 23 of 2024 and its Attachments, Article 7 of Presidential Regulation No. 74 of 2013, and Article 28 of Minister of Trade Regulation No. 20 of 2014. To implement this authority, the Regency/City Government needs to form Regional Regulations and Regional Head Regulations to provide legal certainty for the implementation of alcoholic beverage sales businesses and legal protection for the community in the region